DOI: 10.11606/d.9.2009.tde-07072009-093910
|View full text |Cite
|
Sign up to set email alerts
|

Perfil tecnológico de cepas de bifidobactéria em cultura pura e em co-cultura com Streptococcus thermophilus em leites orgânico e convencional

Abstract: Perfil tecnológico de cepas de bifidobactéria em cultura pura e em cocultura com Streptococcus thermophilus em leites orgânico e convencionalcolony forming units (CFU). mL -1 . The organic milk had higher levels of iron and protein, whereas conventional milk had higher levels of fat and lactose. The main fatty acids were not influenced by the type of milk and higher amounts of conjugated linoleic acid (65% higher than the control) were found in organic fermented milk with the strain BB12 in co-culture with S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…not supplemented milk). Meanwhile, Florence [14] found that for fermentation carried out with pure cultures of bifidobacteria and L. bulgaricus in which fermentation times were very long (T pH4.7 > 10 h), no significant increase in CLA amounts was found in both milks (conventional and organic) after the process. Then, probably there is a factor in organic milk which stimulates fast fermentation and allows metabolic biohydrogenation pathway of CLA production.…”
Section: Correlation Between Linoleicmentioning
confidence: 99%
“…not supplemented milk). Meanwhile, Florence [14] found that for fermentation carried out with pure cultures of bifidobacteria and L. bulgaricus in which fermentation times were very long (T pH4.7 > 10 h), no significant increase in CLA amounts was found in both milks (conventional and organic) after the process. Then, probably there is a factor in organic milk which stimulates fast fermentation and allows metabolic biohydrogenation pathway of CLA production.…”
Section: Correlation Between Linoleicmentioning
confidence: 99%